The use of Pharmacokinetic and Pharmacodynamics to evaluate The recommended dosing regimens of Cefoperazone-Sulbactam in patients with hospital-Acquired Pneumonia - Narawadee Niamhun (Chulalongkorn University, 2014)
Thesis (Ph.D.)--Chulalongkorn University, 2007